Pengaruh Model Pembelajaran Problem Posing terhadap Peningkatkan Kemampuan Multirepresentasi Siswa pada Materi Gelombang Bunyi - Diah Ainun Kurnia; Nanda Novita; Nuraini Fatmi; Safriana Safriana; Widya Widya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Physics learning requires students’ multirepresentational ability to understand concepts through verbal, mathematical, pictorial, or graphical forms. However, instruction at SMAN 1 Natal is still dominated by conventional methods, resulting in less active student participation and low multirepresentational skills. This study aims to determine the improvement of students’ multirepresentational ability after the implementation of the Problem Posing learning model on the topic of sound waves. The research employed a quantitative approach with a quasi-experimental design. The sample consisted of class XI MIPA 1 as the control class and class XI MIPA 2 as the experimental class. The research instrument was a multirepresentation test administered through pre-test and post-test. Data were analyzed using the Shapiro–Wilk test, the Mann–Whitney test, and the N-Gain test. The results of the normality test indicated that the data were not normally distributed; therefore, hypothesis testing was continued using the Mann–Whitney test, which yielded a significance value of 0.00 < 0.05. This result indicates a difference in the improvement of multirepresentational ability between the experimental and control classes. The N-Gain result for the experimental class was 49.40%, categorized as moderate. Thus, the implementation of the Problem Posing learning model in the experimental class resulted in an improvement that was lower than that of the control class